Pengembangan Dashboard Pengelolaan Sampah Berbasis Komposisi Di Tempat Pembuangan Akhir (TPA): Data Visualization for Optimizing Waste Management at Landfills (TPA - Syakira, Riliva; Beny Beny, Beny Beny; Husaein, Ahmad (LPPM Universitas Dinamika Bangsa, 2025)
Waste management is becoming an increasingly pressing global issue, especially in developing countries like Indonesia. Waste that is not managed properly can have various negative impacts on the environment. This condition is increasingly challenging, especially at the regional level, where management agencies often do not have adequate tools to analyze data comprehensively. The available data is often only stored in raw formats, such as spreadsheet files or manual reports. This not only hinders rapid analysis but also has the potential to cause errors in data interpretation. An interactive dashboard based on information technology using the Power BI platform is one relevant approach to addressing this problem which is expected to increase efficiency in data analysis and provide deeper insights through intuitive visualization. The results of this study present an interactive dashboard where waste management data can be arranged and visualized dynamically. Based on the visualized data, the largest total waste generation was found in East Java province with a total daily waste accumulation of 68.67 K with the largest average volume of waste being household waste and the largest waste composition being food waste, then the largest total managed waste was found in East Java province with a total of 14.56 M managed waste and 119.15% the highest recycling rate. The largest green open space was also found in East Java province with a green open space area of ​​1.39 M. Data from the Dashboard is expected to be useful for users, both from the government, companies, and the community, to be able to understand trends and main indicators of waste management quickly and accurately.